Consistent Technique Limits Suspension Laryngoscopy Complications - Larner, Sean P.; Fornelli, Rick A.; Griffith, Shane D. (International Archives of Otorhinolaryngology, 2019)
Introduction Suspension laryngoscopy (SL) is a commonly performed procedure among otolaryngologists. Several studies have shown that adverse effects occur regularly with SL.Objective To evaluate the postoperative complications of SL, and to determine if protecting the dentition and the oral mucosa and limiting suspension times decrease the overall incidence of oral cavity and pharyngeal complications of SL.Methods All of the cases of SL performed by 1 surgeon from November 2008 through September 2014 were retrospectively reviewed. A consistent technique for dental and mucosal protection was utilized, and suspension times were strictly limited to 30 consecutive minutes. The incidence of postoperative complications was calculated and analyzed with respect to gender, smoking status, dentition, laryngoscope type, and suspension system.Results A total of 213 consecutive SL cases were reviewed, including 174 patients (94 male, 80 female). The overall postoperative complication rate was of 3.8%. Four patients experienced tongue-related complications, two experienced oral mucosal alterations, one had a dental injury, and one experienced a minor facial burn. The complication incidence was greater with the Zeitels system (12.5%) compared with the Lewy suspension system (3.3%), although it was not significant (p = 0.4). Likewise, the association of complications with other patient factors was not statistically significant.Conclusion Only 8 out of 213 cases in the present series experienced complications, which is significantly less than the complication rates observed in other reports. Consistent and conscientious protection of the dentition and of the oral mucosa and limiting suspension times to 30 minutes are factors unique to our series that appear to reduce complications in endolaryngeal surgery.
Keywords: suspension laryngoscopy; endolaryngeal surgery; suspension microlaryngoscopy; laryngoscopy complications